Globally Trading Firms in Canada: Productivity and Global Value Chains - Acharya, Ram C. (Journal of Comparative International Management)

(untitled) (Management Futures, 2019)
Using firm-level data in Canada from 2002 to 2008, I compare the economic performance of three types of firms: those that both export and import (called globally trading firms—GTFs), exporters-only, and importers-only. The results show that GTFs are more productive, larger, more capital intensive, pay higher wages, trade more goods, and trade with more countries than both types of one-way traders. These premia for GTFs were found even before they turned into GTFs (self-selection). Moreover, even after turning into GTFs, the productivity growth of a subset of them was faster than that of one-way traders. The higher the involvement in global value chains (GVCs), the higher was the performance of the “learning-by-turning GTFs”. The GTFs with higher productivity growth were the ones that imported from multiple countries, not those that imported only from China. By another measure, they were both-in-both GTFs—those that traded both final and intermediate goods, and in both directions (exports and imports). Even though they employed only 10% of Canada’s business sector workforce, they contributed 60% of its labour productivity growth.